Factors that limit access to higher education - Chesme-Loor, Jacinto Javier; Alcívar-Castro, Eddie José (International research journal of management, IT and social sciences, 2025)
The research focused on identifying the factors that hinder access to higher education for graduates of the Educational Unit Eugenio Espejo, located in the San Sebastián parish, Pichincha canton, Manabí province, during the 2022-2023 period. Through surveys administered to students and teachers, and an interview with the principal, the main limitations faced by young high school graduates in the transition from secondary to higher education were investigated, a stage considered a crucial point in their academic career. The study classified the limiting factors into socioeconomic, academic, institutional, and personal dimensions, all of which have a direct impact on the development and standard of living of students. Descriptive research was adopted, with a mixed approach (qualitative and quantitative), supported by the survey method and the application of a questionnaire as a technique for the analysis and interpretation of the information. The results show that high school graduates’ aspirations for higher education are restricted primarily by adverse socioeconomic conditions, the complexity of admissions tests (such as the ENES), which create unequal opportunities for students from working-class backgrounds, and limited knowledge about the application process.